THE EFFECTS OF LEARNING EXPERIENCE ON MATHEMATIC SELF-CONCEPT OF FIFTH GRADE ELEMENTARY SCHOOL STUDENTS IN YOGYAKARTA CITY AND BANTUL REGENCY - Kiki Vista Devi; Danuri Danuri (Universitas PGRI Yogyakarta, 2022)
This research aims to 1) find out the mathematics learning experience, 2) find out the mathematic self-concept, and 3) investigate the effect of mathematics learning experience towards mathematic self-concept at fifth grade elementary school students in Yogyakarta City and Bantul Regency. This research was conducted in the academic year of 2020/2021. This study used a quantitative survey research technique with a sample of 794 fifth grade elementary school students in the regions. The analysis technique used was descriptive analysis technique, prerequisite test, and simple linear regression analysis with a significance level (Î±) = 0.05. Based on the findings, it can be concluded that in both regions, 1). there is a high category in mathematics learning experiences among the students with a percentage of 52,77%, 2) a moderate category of mathematic self-concept of Â the students is in a percentage of 42,95% and 3) there is an effect of mathematics learning experiences on mathematic self-concept which is shown by the positive and linear independent variable, Y = 18.459 + 0.555 with a significance 0,000, if the value of the studentâ€™s mathematics learning experience is high, the mathematic self-concept will follow the high of experience and vice versa.